1990
DOI: 10.1080/00071669008417309
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding technique,ad libitum, dry or wet force feeding, on the metabolisable energy values of raw materials for poultry

Abstract: 1. Metabolisable energy values (AME, AMEn, TME and TMEn) of three raw materials (maize, sunflower meal and soyabean meal) were determined in adult cockerels using two classical feeding e techniques (ad libitum and force-feeding of dry food) and a new one in which birds were force-fed wet diets. 2. In the wet force-feeding assay nitrogen balances and food intakes were similar to those achieved with ad libitum feeding. The duration of the assay using wet force-feeding was only 2 d as compared to the 3 or 7 d exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
5

Year Published

1991
1991
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 18 publications
0
14
1
5
Order By: Relevance
“…Its chemical composition was: dry matter 940 g/kg, crude protein 90·1 g/kg, crude fat 20·1 g/kg and crude fibre 20·6 g/kg. Maize samples were precision-fed according to the bioassay methods described by Sibbald (1976) and Lessire (1990). Birds were not fed for 24 h to assure that no food residues remained in their alimentary tracts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Its chemical composition was: dry matter 940 g/kg, crude protein 90·1 g/kg, crude fat 20·1 g/kg and crude fibre 20·6 g/kg. Maize samples were precision-fed according to the bioassay methods described by Sibbald (1976) and Lessire (1990). Birds were not fed for 24 h to assure that no food residues remained in their alimentary tracts.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, 6 birds of each sex of both lines were fasted for estimation of endogenous energy excretion. Another method used for determining the bioavailable energy of maize samples was the wet precision-feeding method of Lessire (1990). According to this method water was gradually added to ground maize until a homogeneous mixture was obtained.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some investigators e.g. Lessire et al (1990) observed that feed restriction tended to improve protein, fat, and starch digestibilities irrespective of the diet. However, slower movement speed can increase the chyme residence time in the gut and help nutrient absorption.…”
Section: Disscussionmentioning
confidence: 99%
“…Water was added carefully to the meal and mixed in order to obtain an homogeneous paste. The force-feeding technique and equipment (a force-feeding gun) were similar to those described by Lessire (1990). During the force-feeding experimental period, water was available for ad libitum intake, and trays were positioned under cages for excreta collection.…”
Section: Birds and Managementmentioning
confidence: 99%